The relationship between entrepreneurial learning and entrepreneurial competence: The mediating role of psychological capital - Ngô Thành Trung; Vũ Hữu Thành (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh)
This study investigates the relationship between entrepreneurial learning, psychological capital, and entrepreneurial competence among entrepreneurs in Vietnam. Data was gathered through interviews with 471 entrepreneurs currently operating business initiatives. The relationships between concepts were estimated using Partial Least Squares Structural Equation Modeling (PLS-SEM). Psychological capital and entrepreneurial capacity are high-order constructs; therefore, research employs two-stage techniques to assess these models. According to the findings, entrepreneurial learning positively impacts entrepreneurial competence and psychological capital. The study also discovered psychological capital's statistically significant positive effect on entrepreneurial competence. Furthermore, psychological capital serves as a mediator in the relationship between entrepreneurial learning and entrepreneurial competence. Finally, the research suggests some recommendations to improve entrepreneurial competence.